2013
DOI: 10.1016/j.biopsych.2013.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Neural Connectivity During an Attention Bias Task Moderate Associations Between Early Childhood Temperament and Internalizing Symptoms in Young Adulthood

Abstract: Background Biased attention to threat is found in both individuals with anxiety symptoms and children with the childhood temperament of behavioral inhibition (BI). Although perturbed fronto-amygdala function is implicated in biased attention among anxious individuals, no work has examined the neural correlates of attention biases in BI. Work in this area may clarify underlying mechanisms for anxiety in a sample at risk for internalizing disorders. We examined the relations among early childhood BI, fronto-amyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 61 publications
8
125
1
Order By: Relevance
“…This includes motor response patterns, markers of activity in the autonomic nervous system (ie, heart rate and vagal tone; Kagan et al, 1987), cortical activity patterns (Calkins et al, 1996;McManis et al, 2002), and neuroendocrine profiles (ie, cortisol; Kagan et al, 1988;Schmidt et al, 1997). Recent advances in neuroscience have allowed this original amygdala-based model to be expanded to include broader perturbations in a distributed neural circuit, encompassing components of the PFC and striatum (Bar-Haim et al, 2009;Bishop et al, 2004;Guyer et al, 2006;Hardee et al, 2013;Helfinstein et al, 2012). Common across these diverse models is an emphasis on the relations between BI and hypersensitivity in neural circuitry rapidly engaged by automatic modes of processing and a resulting behavioral sensitivity to motivationally salient cues.…”
Section: Attention Orienting In Bimentioning
confidence: 99%
See 2 more Smart Citations
“…This includes motor response patterns, markers of activity in the autonomic nervous system (ie, heart rate and vagal tone; Kagan et al, 1987), cortical activity patterns (Calkins et al, 1996;McManis et al, 2002), and neuroendocrine profiles (ie, cortisol; Kagan et al, 1988;Schmidt et al, 1997). Recent advances in neuroscience have allowed this original amygdala-based model to be expanded to include broader perturbations in a distributed neural circuit, encompassing components of the PFC and striatum (Bar-Haim et al, 2009;Bishop et al, 2004;Guyer et al, 2006;Hardee et al, 2013;Helfinstein et al, 2012). Common across these diverse models is an emphasis on the relations between BI and hypersensitivity in neural circuitry rapidly engaged by automatic modes of processing and a resulting behavioral sensitivity to motivationally salient cues.…”
Section: Attention Orienting In Bimentioning
confidence: 99%
“…This interaction of BI and emotion condition only held under relatively short stimulus presentation conditions suggesting that BI is specifically associated with early, automatic, and reactive attention biases. Similarly, using a subsample of these participants in early adulthood, Hardee et al (2013) used the dot-probe task to link BI to fronto-amygdala connectivity. In this study, fronto-amygdala connectivity was more variable in BI than non-BI subjects, when contrasted across threat and no-threat events appearing in the dot-probe task.…”
Section: Attention Orienting In Bimentioning
confidence: 99%
See 1 more Smart Citation
“…Converging evidence from a series of neuroimaging, electrocortical, and behavioral studies in shy adults and children suggest that temperamental shyness is associated with affect-related attentional biases to potential threat. For example, fMRI studies in shy and behaviorally inhibited adults using socially threatening stimuli that are theoretically immediately threatening, including unfamiliar and angry faces, have found greater amygdala activation (Schwartz, Wright, Shin, Kagan, & Rauch, 2003) and shorter response latencies (Beaton et al, 2008); differential amygdalar connectivity (Hardee et al, 2013); as well as differential patterns of neural activation as a function of morning cortisol changes among shy-sociable [e.g., rostal anterior cingulate cortex (ACC)] and shy-unsociable adults (e.g., amygdala, insula, posterior ACC) (Tang, Beaton, Schulkin, Hall, & Schmidt, 2014).…”
Section: Shyness and Sensitivity To Threatmentioning
confidence: 99%
“…FMRI studies that have included behaviorally inhibited youth find similar fronto-limbic perturbations as those described in youth with SAD. Notably, studies with adolescents with BI have reported increased responses in the amygdalae to negative emotional expressions, differential striatal responses to the anticipation of monetary and social rewards, and during conflict adaptation (when individuals habituate to successively presented contradictory emotional information) ( Bar-Haim et al, 2009;Guyer et al, 2014;Hardee et al, 2013;Helfinstein et al, 2011;Jarcho et al, 2013aJarcho et al, ,b, 2014Pérez-edgar et al, 2007).…”
Section: G Modelmentioning
confidence: 99%